The genome sequence of a chironomid fly, Chironomus tentans Fabricius, 1805 [version 1; peer review: 2 approved, 1 approved with reservations] - Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a specimen of Chironomus tentans (chironomid fly; Arthropoda; Insecta; Diptera; Chironomidae). The genome sequence has a total length of 185.47 megabases. Most of the assembly (99.7%) is scaffolded into 4 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 16.09 kilobases. Gene annotation of this assembly on Ensembl identified 12,575 protein-coding genes.